1953
DOI: 10.1085/jgp.37.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Protein in the Pancreas

Abstract: 1. The ribonucleoprotein of the microsome fraction which sediments at 40,000 R.P.M. as a pellet (and which is referred to as the pellet material) has been studied with reference to its role in protein synthesis in the pancreas. 2. In pellet material nucleic acid and protein form a definite complex as shown by its electrophoretic behavior and unchanging composition under various conditions. 3. Protein of pellet material is not especially rich in the diamino acids. 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1955
1955
2004
2004

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Several conflicting results concerning the effect of stimulation of pancreatic secretion on the rate of protein synthesis have been published in the past (Daly & Mirsky, 1953;Allfrey et al, 1954;Ferreira et al, 1955 ;Farber & Sidransky, 1956;Hokin, 1956;Busch et al, 1959;Stocker, 1962;Webster & Tyor, 1966;Peakall, 1967;Webster, 1968;Kramer & Poort, 1968;Poort & Geuze, 1969;Poort & Kramer, 1969). As pointed out by Poort & Kramer (Kramer & Poort, 1968;Poort & Kramer, 1969) it is possible to reconcile most of the discrepancies by taking into account the fact that in a protein-secreting gland the amount of protein present Values given are averages ±S.E.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several conflicting results concerning the effect of stimulation of pancreatic secretion on the rate of protein synthesis have been published in the past (Daly & Mirsky, 1953;Allfrey et al, 1954;Ferreira et al, 1955 ;Farber & Sidransky, 1956;Hokin, 1956;Busch et al, 1959;Stocker, 1962;Webster & Tyor, 1966;Peakall, 1967;Webster, 1968;Kramer & Poort, 1968;Poort & Geuze, 1969;Poort & Kramer, 1969). As pointed out by Poort & Kramer (Kramer & Poort, 1968;Poort & Kramer, 1969) it is possible to reconcile most of the discrepancies by taking into account the fact that in a protein-secreting gland the amount of protein present Values given are averages ±S.E.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies dealing with the effect of stimulation of enzyme secretion on the rate of protein synthesis in the pancreas have been reported (Daly & Mirsky, 1953;Allfrey, Daly & Mirsky, 1954;Ferreira Fernandez & Junqueira, 1955;Farber & Sidransky, 1956;Hokin, 1956;Busch, Allen & Anderson, 1959;Stocker, 1962;Webster & Tyor, 1966;Peakall, 1967;Webster, 1968;Kramer & Poort, 1968;Poort & Geuze, 1969;Poort & Kramer, 1969). Though several conflicting results have been obtained in the past, recent studies seem to indicate that a substantial increase of the rate of protein synthesis is brought about by either feeding or pharmacological stimulation of secretion only in birds and frogs (Webster & Tyor, 1966: Peakall, 1967Webster, 1968;Poort & Geuze, 1969); whereas in mammals protein synthesis proceeds at a constant rate, independently of secretion (Kramer & Poort, 1968;Poort & Kramer, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Radioactive labelled amino-acids given intravenously to experimental animals are rapidly taken up by the acinar cells of the pancreas (Allfrey et al, 1953;Junquiera et al, 1955). Hansson (1959) gave intravenous 35S-methionine to a variety of experimental animals and showed preferential uptake of the aminoacid by the pancreas, the radioactivity per gramme of tissue in this organ being six to eight times that in the next most active oigan, the liver.…”
Section: Introductionmentioning
confidence: 99%
“…It is now well-established that alkaline phosphatase is particularly rich in the cells which are engaged in the synthesis of fibrous protein (JOHNSON et al 1945, BRADFIELD 1946, JEENER 1948, and ELLIS et al 1956, and that the presence of ribonucleic acid (RNA)-protein is an essential factor for protein synthesis (ALLFREY et al 1953, BORSOOK 1954, GALE and FOLKES 1954, ZAMECNIK and KELLER 1954, ALLFBEY et al 1955, BRACHET 1957, MIURA et al 1957and STICH and PLAUNT 1958. Moreover, an intimate association of alkaline phosphatase with RNA in the synthesis of fibrous proteins has been pointed out by some workers (BRACHET 1942, FELL and DANIELLI 1943and BRADFIELD 1950, POSALAKY et al (1951) reported that in the lens-regenerating process of the newt, the activity of alkaline phosphatase increases gradually in the retina, recording a peak on the 14th day after lens-extirpation and then decreases to the level of the non-operative eye.…”
Section: Discussionmentioning
confidence: 99%